2020
DOI: 10.25259/sni_415_2019
|View full text |Cite
|
Sign up to set email alerts
|

Primary Ewing’s sarcoma of the petroclival bone: A case report and literature review

Abstract: Background: Primary Ewing’s sarcoma (ES) is typically seen within the long bones, vertebrae, or pelvis. Uncommonly, it can be found within the cranium among the rarest locations for primary ES are the skull base, in particular, the petroclival bone. Case Description: The patient is a 68-year-old female with past medical history of Stage III breast cancer who presented with severe retro-orbital headache and diplopia due to a cranial nerve VI palsy. Magnetic resonance imaging (MRI) revealed a mass at the left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…1 Our English MEDLINE online literature review identified only 13 cases of primary intracranial Ewing's sarcoma in patients of age 50 years or older (Table 1). 5,8,10,[16][17][18][19][20][21][22][23][24] The mean (standard deviation) age of these patients was 59.2 (8.2) years. Male to female ratio was 8:5 (61.6%:38.4%) Of these patients, only 3 (23%) were of age similar to or older than our patient.…”
Section: Discussion Observationsmentioning
confidence: 99%
“…1 Our English MEDLINE online literature review identified only 13 cases of primary intracranial Ewing's sarcoma in patients of age 50 years or older (Table 1). 5,8,10,[16][17][18][19][20][21][22][23][24] The mean (standard deviation) age of these patients was 59.2 (8.2) years. Male to female ratio was 8:5 (61.6%:38.4%) Of these patients, only 3 (23%) were of age similar to or older than our patient.…”
Section: Discussion Observationsmentioning
confidence: 99%
“…Primary ESs of skull base involvement are extremely rare, and to date, only three cases of primary ES of the petroclival bone have been reported [ Table 1 ]. [ 1 , 7 , 8 ] The four reported cases include two male and two female patients. Most of patients are younger with a median age of 23 years (14–72).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding surgical management, previous reports have recommended that tumor resection should be as radical as possible. [ 1 , 6 , 7 ] However, radical tumor resection may be difficult in skull base lesions due to the inclusion of or proximity to critical structures. Among the current treatment protocols for primary ES, multimodal treatment including a combination of radiation therapy, chemotherapy, and surgery can result in a cure rate of ≥50%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations